2011
DOI: 10.1002/app.34544
|View full text |Cite
|
Sign up to set email alerts
|

Double metal cyanide complexes synthesized by solvent‐free grinding method for copolymerization of CO2 and propylene oxide

Abstract: Two active double metal cyanide (DMC) complexes were successfully synthesized by solvent-free grinding method. Their structures were characterized by FTIR spectrometer and X-ray diffractometer. The results showed that Complex 1 (double metal cyanide complex with K 3 Fe(CN) 6 and ZnCl 2 ) and Complex 2 (double metal cyanide complex with K 3 Fe(CN) 6 and Zn(CH 3 COO) 2 ) had the same structures, crystal forms, and lower crystallinity as both of them synthesized by conventional solvent-based methods, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 56 publications
0
16
0
Order By: Relevance
“…It should be noted that the powder pattern reported by Zhang et al 53 of a DMC obtained by ball milling K 3 [Fe(CN) 6 ] and zinc acetate (complex 2 in ref. 53) is qualitatively similar to the diffraction pattern of L-DMC. We therefore suggest that the structure they observed during ball milling is an Fe(CN) 6 analogue of our layered phase.…”
Section: Structure Solution and Renementmentioning
confidence: 98%
“…It should be noted that the powder pattern reported by Zhang et al 53 of a DMC obtained by ball milling K 3 [Fe(CN) 6 ] and zinc acetate (complex 2 in ref. 53) is qualitatively similar to the diffraction pattern of L-DMC. We therefore suggest that the structure they observed during ball milling is an Fe(CN) 6 analogue of our layered phase.…”
Section: Structure Solution and Renementmentioning
confidence: 98%
“…We demonstrated that the carbonate fraction could be increased up to 64% by employing a dual catalytic system composed of a DMC and a Salen‐cobalt(III) complex . In this work, we report the simple preparation of a new type of DMC catalyst, which exhibits a high CO 2 incorporation (up to 67 mol %) and thus provides a successful derivatization of the conventional DMC catalyst …”
Section: Introductionmentioning
confidence: 95%
“…In this regard, the simple and efficient process of mechanochemistry has proven to be effective in activating the copolymerization of CO 2 and epoxides. [28][29][30][31] Catalysts can be synthesized for polycarbonates using a metal complex. They can also be used together with a cocatalyst to enhance their performance in a binary catalyst system.…”
Section: Introductionmentioning
confidence: 99%